A Compass to Prosperity : The Next Steps of Euro Area Economic Integration. (International Monetary Fund, 2018)
A speech delivered by the IMF's Managing Director Christine Lagarde at the German Institute for Economic Research (DIW) as part of the Institute's Europe Lecture Series in Berlin, Germany, on March 26, 2018.